DIGITAL TRANSFORMATION IN PROFESSIONAL HIGHER EDUCATION - Voloshka , Yevheniia (Global Prosperity, 2023)
The article analyzes the role of digital technologies in the modernization of the educational process, which becomes an urgent task in the context of modern social and technological challenges. The relevance of the topic is emphasized by the changes caused by the global pandemic of COVID-19 and the full-scale invasion of Russia on the territory of Ukraine, which significantly accelerated the need for the introduction of distance learning and the use of digital innovations in the educational process. Digital transformation is considered as a multifaceted process, which includes not only technological renewal, but also pedagogical adaptation to new forms of education. An important element is the development of digital competences, which are identified as key for the successful adaptation of graduates to the requirements of the labor market. Modern challenges related to digital transformation are characterized, in particular, attention is focused on the importance of developing the pedagogical competence of scientific and pedagogical workers in the context of new technologies, and the importance of an individual approach to learning, the integration of interactive methods, and the use of big data analytics to optimize educational processes is emphasized. Conclusions are formulated and it is determined that the digital transformation in vocational higher education, which is a response to modern educational challenges, is largely based on the role of public authorities. The role of public authorities in the digitalization of vocational higher education is strategically important and multifaceted. Public authorities not only form the regulatory foundation that determines the directions and standards of digitalization, but also provide financial and technical support for its implementation. This includes the development of infrastructure, the provision of equipment and resources for digital learning, as well as investment in the development of professional skills and competencies of teachers. Public authorities also initiate and support partnerships with the private sector that allow for the integration of innovative technologies and practices into the educational process. These collaborations often focus on the development and implementation of interactive platforms, distance learning, and other digital tools. The directions of further research are determined, in particular, the development of effective approaches to the implementation of digital tools in vocational pre-university education.